2017
DOI: 10.18869/nirp.ijmtfm.7.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Posterior Curve Length of Sternum and Stature: A Postmortem Study in Delhi Population

Abstract: Background:The primary characteristics to establish the identification of an individual are sex, age, and stature [1]. Determination of stature is easy if a complete body or the entire skeleton is found. When only some parts of the body or skeleton are available, it is necessary to have different formulae for determination of stature from their osteometric measurements. The present study aims to assess the stature of an individual from his or her sternum with the help of Posterior Curve Length (PCL). Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…The study population, sample size and mean length of cadaver (Stature) observed in the other Indian studies is charted in Table 3. The mean length of male cadavers observed by Singh J et al 12 , Menezes RG et al 10,11 , Ranjith Raj VP et al 14 and Saraf A et al 15 is comparatively on the higher side than that observed by Tumram NK et al 16 , Baraw R et al 17 and in the present study. The mean length of female cadavers is observed to be relatively similar in all the studies except that of Saraf A et al 15 (Table 3).…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…The study population, sample size and mean length of cadaver (Stature) observed in the other Indian studies is charted in Table 3. The mean length of male cadavers observed by Singh J et al 12 , Menezes RG et al 10,11 , Ranjith Raj VP et al 14 and Saraf A et al 15 is comparatively on the higher side than that observed by Tumram NK et al 16 , Baraw R et al 17 and in the present study. The mean length of female cadavers is observed to be relatively similar in all the studies except that of Saraf A et al 15 (Table 3).…”
Section: Discussionsupporting
confidence: 44%
“…They concluded that the length of the sternum is a strong correlating factor to the stature of South Indian adolescent male population and it is useful for anthropologists and medico-legal experts for stature estimation. Baraw R et al 17 and Ranjith Raj VP et al 14 observed strong correlation coefficients in their study while in both the studies the sternal measurements were taken including the xiphoid process which has high variability in its length. 13 However, Marinho Let al 19 reported a correlation of 0.329 on fresh sterna sample in a male which also includes the xiphoid process.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations